EFL Teachers of Junior High School Readiness in Applying â€œMerdeka Curriculumâ€ - Irma Herawati (UM Purwokerto Press, 2023)
Curriculum is the heart of schoolsâ€™ activity. It influences what will the students learn, experience and what kinds of output will the schools have. Meanwhile, the studentsâ€™ conditions are always change time after time. Therefore, the curriculum needs to be aligned with the students. In the pandemic situation which changes the way the teaching-learning process, there is a fact that the online learning caused â€œlearning lossâ€. This condition threats the studentsâ€™ achievement. The government released â€œMerdeka curriculumâ€ as a solution to overcome the problem. The teacher as the â€œmain actorâ€ in doing the curriculum must have good understanding about it. Therefore, the research was conducted to know the EFL teachers of Junior high school readiness in the application of â€œMerdeka curriculumâ€ in their class. The respondents of this research were the EFL teachers of Junior high school in Purbalingga regency. A closed questionnaire was distributed through Whatsapp group to 60 EFL teachers. The result showed that 72, 08% EFL teachers were ready to apply â€œMerdeka curriculumâ€.